The Effect of Diabetes on Ankle Fracture Outcomes in the UK: A National Collaborative Assessment of Current Guidelines, Management and Surgical Choices in Ankle Fractures. Issue 4 (November 2022) - Reichert, Ines; Ahluwalia, Raju S.; Wek, Cesar; Stringfellow, Thomas; Coffeyy, Duncan; Tan, Sze Ping
Category: Trauma; Ankle Introduction/Purpose: Objectives: Ankle fractures associated with diabetes experience more complications with standard Open-Reduction-Internal-Fixation (ORIF) following AO-principles than those without diabetes. It is unclear if augmented/extended fixation strategies can improve this. This aim of this study was to understand utilisation of extended/augmented/ORIF techniques (e.g., hind-foot-nail (HFN) and present outcomes of ankle fractures associated with diabetes. Secondarily the study aimed to evaluate compliance with national guidelines on early post-operative weight bearing. Methods: Research, Design & Methods: A national-multicentre retrospective cohort study was conducted between Jan - Jun 2019 of 56 UK centres (10 Major-Trauma-Units and 46 Trauma-Units). Institutional approval was obtained by all centres. 1360 complex-ankle-fractures were enrolled. Demographics, fixation choice and surgical outcomes were obtained. Statistical analysis was performed including propensity matching comparing patients with and without diabetes. Results: 316pts (23.2%) had diabetes, 7.4% had neuropathy, with a mean age 63.9yrs (vs.49.3yrs in non-diabetes), with greater frailty >4 (24% vs.14% (non-diabetes) (p<0.03). 79.7% underwent standard AO-principles-ORIF; those with peripheral neuropathy were more likely to undergo extended/augmented-techniques. Overall wound complications were higher with diabetes (15.8% vs. 8.8% (p<0.02). 13% of patients with diabetes underwent augmented/extended techniques without a difference in complications to a matched control group without diabetes. Conclusion: Diabetic ankle fractures occur in older, frailer persons; whilst lower than expected neuropathy rates suggest a need for improved assessment. Contrary to current guidelines most patients remain non-weightbearing post-surgery. Extended/Augmented surgical techniques can allow earlier weight-bearing without increasing complications. MDT screening/management may improve surgical selection and under-utilisation of these techniques and promote early mobilisation.